GEWEKShAQLILAR (BOVIDAE) GELMINTLER FAUNASÍNÍŃ TROFIKALÍQ-EKOLOGIYALÍQ SÍPATLAMASÍ (QARAQALPAQSTAN MÍSALÍNDA) - Ubbiniyazova, Jamila Komekbaevna (ILIM hám JÁMIYET, 2026)
The article examines the trophic and ecological characteristics of the helminth fauna of bovidae in Karakalpakstan. As a result of the research, 36 species of helminths found in domestic (Ovis aries dom., Capra hircus dom., Bos taurus dom.) and wild (Saiga tatarica, Gazella subgutturosa) representatives of ungulate animals were identified, and their classification based on their transmission mechanisms was developed. Based on the analysis of helminth species composition, the priority role of topical connections in the destruction of the final host was determined. The absence of trophic links in the life cycles of the studied parasites indicates the evolutionary adaptation of the helminth fauna of hollow-horned animals to the pasture type of nutrition.